RNA binding proteins as mediators of pathological cardiac remodeling - Acharya, Pooja; Parkins, Sharon; Tranter, Michael (Frontiers in Cell and Developmental Biology, 2024)
RNA binding proteins (RBPs) play a central in the post-transcriptional regulation of gene expression, which can account for up to 50% of all variations in protein expression within a cell. Following their binding to target RNAs, RBPs most typically confer changes in gene expression through modulation of alternative spicing, RNA stabilization/degradation, or ribosome loading/translation rate. All of these post-transcriptional regulatory processes have been shown to play a functional role in pathological cardiac remodeling, and a growing body of evidence is beginning to identify the mechanistic contribution of individual RBPs and their cardiac RNA targets. This review highlights the mechanisms of RBPdependent post-transcriptional gene regulation in cardiomyocytes and fibroblasts and our current understanding of how RNA binding proteins functionally contribute to pathological cardiac remodeling.